The Rapid Discrimination and Quality Assessment of Three Zanthoxylum Species Using 1H NMR Spectrometry - Hyeon Seok Jang; Birang Jeong; Seong Yeon Choi; Jiho Lee; Yong Soo Kwon; Heejung Yang (International Journal of Analytical Chemistry)
The husks and fruits of Zanthoxylum species (Rutaceae) are the popular pungent and spicy ingredients of foods and the traditional medicines in many countries. Three Zanthoxylum species, Z. bungeanum, Z. schinifolium, and Z. piperitum, are distributed and intermixed with each other as “Zanthoxyli Pericarpium” in Korean markets. In the present study, we analyzed the ethyl acetate-soluble and nonpolar fractions of Zanthoxylum samples by 1H NMR spectrometry and performed a multivariate analysis for finding the discriminant markers between three species. Xanthoxylin was identified as the metabolic marker for the discrimination of Zanthoxylum species and quantified by the qNMR approach.